FIRST DIRECTIONAL ARCHAEOMAGNETIC RESULTS FROM SYRIA: EVIDENCE FROM TELL MISHRIFEH/QATNA - Speranza F.; Maritan L.; Mazzoli C.; Morandi Bonacossi D.; D'Ajello Caracciolo F. (My University, 2006)
We report on the first archaeomagnetic directional data obtained from Syria. Reliable palaeomagnetic directionswere collected from four pyrotechnological archaeological structures dated by type of pottery and radiocarbon from the 19th to 8th century BC (Middle Bronze to Iron Age) in Tell Mishrifeh/Qatna, Syria. Fairly constant northward declination values (within confidence limits) were obtained, whereas inclination values increased from 42.3° to 73.0° from the Middle Bronze to Iron Age. At first approximation, these new data are consistent with coeval archaeomagnetic directions from Western Europe and Bulgaria. The high inclination (73.0° ± 2.8°) documented for the Iron Age (translating to a VGP latitude of 65.9.N) suggests that very strong secular variation was occurring during the 8th century BC. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: ARCHAEOMAGNETISM; GEOMAGNETIC SECULAR VARIATION; SYRIA